2020
DOI: 10.1186/s43019-020-00075-y
|View full text |Cite
|
Sign up to set email alerts
|

Demographic data is more predictive of component size than digital radiographic templating in total knee arthroplasty

Abstract: Background Preoperative radiographic templating for total knee arthroplasty (TKA) has been shown to be inaccurate. Patient demographic data, such as gender, height, weight, age, and race, may be more predictive of implanted component size in TKA. Materials and methods A multivariate linear regression model was designed to predict implanted femoral and tibial component size using demographic data along a consecutive series of 201 patients undergoing index TKA. Traditional, two-dimensional, radiographic templat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…For the tibial implant size, elastic net penalized linear regression was optimal with 43.8% accuracy. Wallace et al’s study found similar results for predicting TKA intraoperative implant sizes based on demographic data ( Wallace et al, 2020 ). Using linear regression based on patient age, gender, height, weight, and race the predicted component sizes with accuracy of 43.7% for femoral and 43.7% for tibial implant size.…”
Section: Discussionmentioning
confidence: 76%
“…For the tibial implant size, elastic net penalized linear regression was optimal with 43.8% accuracy. Wallace et al’s study found similar results for predicting TKA intraoperative implant sizes based on demographic data ( Wallace et al, 2020 ). Using linear regression based on patient age, gender, height, weight, and race the predicted component sizes with accuracy of 43.7% for femoral and 43.7% for tibial implant size.…”
Section: Discussionmentioning
confidence: 76%
“…[ 23 ] 2021 VR and AR training in knee arthroplasty Preop Review Few assessments of VR training but promising P reoperative planning Wallace et al . [ 24 ] 382 2020 PM Implant Size Preop Component size prediction Sex, height, weight, age, and ethnicity More accurate than radiographic templating Kunze et al . [ 25 ] 17,283 2021 PM Implant size Preop Component size prediction Demographic variables (age, height, weight, BMI, sex) Good to excellent performance for predicting TKA component Size.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Still, the limited predictive factors and limited size of certain products are the drawbacks [ 39 – 41 ]. Demographic-based multivariate linear regression models can be used to predict more accurate implant size than digitally-templated sizes for femoral ( P = 0.04) and tibial ( P < 0.01) components [ 24 ]. The regression models are created using the stochastic gradient boosting model, allowing users to input data and receive individualized sizing predictions and explanations [ 25 ].…”
Section: Review and Discussionmentioning
confidence: 99%
“…Templating is an important exercise in preoperative planning for total knee arthroplasty (TKA), which has clinical, logistical and economic benefits. 1,2 Preoperative templating allows surgeons to choose the most appropriate size of implant that would restore alignment and stability of the knee, resulting in better functional outcomes. 1-3 Templating also facilitates improved theatre efficiency and lower cost; by identifying the implant sizes preoperatively, the correct sizes can be ordered in advance reducing cancellations and intraoperative delays.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, several studies have investigated the use of patient demographics to predict TKA implant size, reporting accuracy within one size in 85–100% of cases. 1,5-7 In spite of its accuracy, surgeons are generally more comfortable viewing radiographs when templating, which allows them to analyse bone loss and deformity.…”
Section: Introductionmentioning
confidence: 99%